Perbaikan Tingkat Kekaburan Gambar Akibat Pembesaran Pada Hasil Creenshot Dengan Metode Unsharp Mask - Soeb Aripin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Screenshot is a display image taken from a monitor screen such as computers, tablet PCs and smartphones. The image results from the screenshot have a low level of sharpness and smoothness. If this image is enlarged, the quality becomes low like blur. To improve the quality of the image so that it is not blurred when enlarged, then the process of sharpening and smoothing. This process will improve the quality of the image to be better. The image that is processed in this research is the image screenshot. Furthermore, the image is processed using digital image processing using Matlab software. The processing stages are crop, image enhancement and unsharp mask. The image of the image enhancement and unsharp mask results are collaborated to increase and increase the sharpness and smoothness of the image in the results of the screenshot image being tested. The results of testing on this method with better sharpness quality with a comparison of images using the mean square error of 0.0627.2404%. The image of the test results can be concluded that the value of the pixels sought has a larger image size than the original and has a resolution greater than the initial image and sharpness and smoothness so that the unsharp mask method can improve the sharpness and smoothness of the image. But the changes produced using the method have not been significant enough.